Initiating renal replacement therapy through incremental haemodialysis: Protocol for a randomized multicentre clinical trial - M. Fernández Lucas; G. Ruíz-Roso; J. L. Merino; R. Sánchez; H. Bouarich; J. A. Herrero; A. Muriel; J. Zamora; A. Collado (Trials, 2020)
Abstract Background Thrice-weekly haemodialysis is the usual dose when starting renal replacement therapy; however, this schedule is no longer appropriate since it does not consider residual renal function. Several reports have suggested the potential benefit of beginning haemodialysis less frequently and incrementally increasing the dose as the residual renal function decreases. However, all the data published so far are from observational studies. Thus, this clinical trial avoids any potential selection bias and will assess the possible benefits that have been observed in observational studies. Methods/design This report describes the study protocol of a randomized prospective multi-centre open-label clinical trial to evaluate whether starting renal replacement therapy with twice-weekly haemodialysis sessions preserves residual renal function better than the standard thrice-weekly regimen. We also explore other clinical parameters, such as concentrations of uremic toxins, dialysis doses, control of anaemia, removal of medium-weight uremic toxins, nutritional status, quality of life, hospital admissions and mortality. Only incident haemodialysis patients who can maintain a urea clearance rate KrU ≥ 2.5 mL/min/1.73 m2 are eligible. Patient recruitment began on 1 January 2017 and will last for 2 years or until the required sample size has been recruited to ensure the established statistical power has been reached. The minimum follow-up period will be 1 year. Anuric patients with acute renal failure and patients who return to haemodialysis after a kidney transplant failure are excluded. It has been calculated that 44 patients should be recruited into each group to achieve a power of 80% in a two-sided comparison of means with a usual significance level of 0.05. A time-to-event analysis will estimate the probability of kidney function survival in both groups using the Kaplan–Meier method. Survival curves will be compared with log-rank tests. This survival analysis will be complemented with a proportional hazard model to estimate the hazard ratio of kidney function survival adjusted for any confounding factors. Analyses will be carried out in accordance with the intention-to-treat principle. Discussion The incremental initiation of dialysis may preserve residual renal function better than the conventional treatment, with similar or higher survival rates, as reported by observational studies. To our knowledge, this is the first clinical trial to evaluate whether initiating renal replacement therapy with twice-weekly haemodialysis sessions preserves residual renal function better than beginning with the standard thrice-weekly regimen. Trial registration ClinicalTrials.gov, NCT03302546. Registered on 5 October 2017.